Educação Infantil e legislação: reflexões acerca de sua aplicabilidade - Sancigollo, Edilaine (Universidade Federal de São Carlos, 2023)
The present work seeks to reflect on the legal foundations for planning the pedagogical practices of teachers in Early Childhood Education, having as references the current legislation that guides pedagogical actions in early childhood education, these documents are the National Curriculum Guidelines for Early Childhood Education and the Criteria for Care in Day Care Centers that respects the Fundamental Rights of Children. To carry out such reflections, it was essential to seek data from professionals in the field of Early Childhood Education, and then an information survey was carried out, using an online form, with eleven Early Childhood Education teachers in the city of Sorocaba. Guided by quantitative and qualitative methodology, the work presents an analysis of the collected data - in order to identify and recognize the rights guaranteed by legal documents, which aim to guarantee a quality education for children from 0 to 5 years and 11 months old.
Early Childhood Education and legislation: reflections on its applicability
Keywords: Educação Infantil; DCNEI; Práticas Pedagógicas; Child Education; Pedagogical Practices; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO